The Effect of Aerobic Exercise on Quantity and Quality of Sleep Among Elderly People Referring to Health Centers of Lar City, Southern of Iran; A Randomized Controlled Clinical Trial - Sharif, Farkhondeh; Seddigh, Maryam; Jahanbin, Iran; Keshavarzi, Sareh (Current Aging Science, 2015)
Background and Objectives: Aging is associated with reduced quality and quantity of sleep. 50% of senior citizens living in the community and 70% of those living in nursing homes suffer from sleep disorders. Moreover, insomnia increases the risk of mortality and morbidity in older adults. We aimed to investigate the effect of aerobic exercise on quantity and quality of sleep among the elderly people referring to health centers of Lar city, southern Iran. Methods and Patients: We enrolled 60 elderly people whose age range was 60-75 years and (mean ±SD) age was (64.8±5.2). Participants were randomly assigned into two groups of 30 each (case group= 30 and control group=30). The patients in the case group participated in exercise trainings consisted of three one-hour sessions per week for 12 consecutive weeks. Sleep quantity and quantity in the participants was evaluated before and after intervention using Pittsburgh Sleep Quality Index (PSQI). Results: Independent t-test showed that sleep quality score was improved by 44.46% in the case group (p<0.0001). Furthermore, sleep duration was improved by 98/16% (p=0.038) and sleep latency was improved by 76/6% in the case group; while, the difference between the two groups regarding the changes in the sleep latency was not statistically significant (p=0.089). Conclusion: Aerobic exercise program could improve the sleep quality and quantity in the elderly. It could also be used as a cost effective and long lasting method of therapy with no side effect which could be used for the treatment of insomnia in older people.
Keywords: elderly